2021
DOI: 10.3390/biomedicines9060652
|View full text |Cite
|
Sign up to set email alerts
|

Gender Specific Differences in Disease Susceptibility: The Role of Epigenetics

Abstract: Many complex traits or diseases, such as infectious and autoimmune diseases, cancer, xenobiotics exposure, neurodevelopmental and neurodegenerative diseases, as well as the outcome of vaccination, show a differential susceptibility between males and females. In general, the female immune system responds more efficiently to pathogens. However, this can lead to over-reactive immune responses, which may explain the higher presence of autoimmune diseases in women, but also potentially the more adverse effects of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 195 publications
(251 reference statements)
0
30
1
Order By: Relevance
“…Though, post-transfusion parasitemia did not statistically associate with these variables. In contrast to the findings in this study, males have been reported to be more susceptible to infectious diseases than females (Klein 2000 ; Altamimi et al 2020 ; Bunders and Altfeld 2020 ; Migliore et al 2021 ). The only attributable reason to this observation of the high incidence of P. falciparum infection in female blood recipients was that disproportionately more female blood recipients than male blood recipients were encountered during the study.…”
Section: Discussioncontrasting
confidence: 99%
“…Though, post-transfusion parasitemia did not statistically associate with these variables. In contrast to the findings in this study, males have been reported to be more susceptible to infectious diseases than females (Klein 2000 ; Altamimi et al 2020 ; Bunders and Altfeld 2020 ; Migliore et al 2021 ). The only attributable reason to this observation of the high incidence of P. falciparum infection in female blood recipients was that disproportionately more female blood recipients than male blood recipients were encountered during the study.…”
Section: Discussioncontrasting
confidence: 99%
“…These pathologies are part of the autoimmune thyroid disorders that show changes in methylation of several genes, gene polymorphisms and also miRNAs identified either specific for each disease or common to both ( 89 ). However, the high preponderance in women of this diseases and in many other autoimmune ones, as well as in experimental animal models, support that the sexual dimorphism in normal and abnormal immune responses could be due to epigenetic alterations in X chromosome ( Box 1 ) which codes for many genes of in the immune system ( 83 , 98 , 99 ). Common features among several autoimmune diseases involve incomplete inactivation of some genes in the X chromosome (XCI), or asymmetric inactivation of X chromosome (skewed XCI) where 75-80 or over 95% of one parent’s chromosome is inactivated ( 98 , 99 ).…”
Section: Sex Dimorphism Of Hpt Axis Activitymentioning
confidence: 97%
“…However, the high preponderance in women of this diseases and in many other autoimmune ones, as well as in experimental animal models, support that the sexual dimorphism in normal and abnormal immune responses could be due to epigenetic alterations in X chromosome ( Box 1 ) which codes for many genes of in the immune system ( 83 , 98 , 99 ). Common features among several autoimmune diseases involve incomplete inactivation of some genes in the X chromosome (XCI), or asymmetric inactivation of X chromosome (skewed XCI) where 75-80 or over 95% of one parent’s chromosome is inactivated ( 98 , 99 ). Analyses of 309 GD and 490 HT female subjects together with meta-analyses of previous reports confirm the increased XCI skewing and extreme skewing in female subjects with GD and HT respectively ( 100 ).…”
Section: Sex Dimorphism Of Hpt Axis Activitymentioning
confidence: 97%
“…Scleroderma, multiple sclerosis, rheumatoid arthritis and asthma, in particular, reflect these gender differences [ 25 , 26 , 27 , 28 , 29 , 30 ]. The incidence and course of systemic lupus erythematosus (SLE) differ between the sexes, with a nine-fold higher incidence in women linked to the influence of estrogen on epigenetic, immune and genetic factors (X-linked genes such as Foxp3, TNF and Tlr7) [ 31 , 32 ]. Hashimoto’s thyroiditis, Graves’ disease, myasthenia gravis, multiple sclerosis and Sjögren’s syndrome are also prevalent in women compared to men [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Sex Differences In Autoimmune Diseases Inflammatory Disorder...mentioning
confidence: 99%